TEACHING ENGLISH IN THE AGE OF ARTIFICIAL INTELLIGENCE: SMART TOOLS, SMART LEARNERS - Bazarova Sevara Rustamovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article analyzes the impact of artificial intelligence (AI) technologies on the English language teaching process, based on the concepts of “smart tools” and “smart learners”. The study examines the effectiveness of AI-based language learning platforms, automatic translation systems, speech recognition technologies, and adaptive learning systems. It also covers the role of the teacher in a modern educational environment, the development of digital literacy, and students’ independent learning abilities. The article analyzes the possibilities and limitations of artificial intelligence in modernizing the English language teaching process.